Flt3 Ligand Induces Monocyte Proliferation and Enhances the Function of Monocyte‐Derived Dendritic Cells In Vitro. Issue 8 (August 2015) - Kim, Sung‐Whan; Choi, Seong‐Mi; Choo, Yee Shin; Kim, Il‐Kwon; Song, Byeong‐Wook; Kim, Han‐Soo
<x xml:space="preserve">Abstract</x> Flt3 ligand (FL), a potent hematopoietic cytokine, plays an important role in development and activation of dendritic cells (DCs) and natural killer cells (NK). Although some post‐receptor signaling events of FL have been characterized, the role of FL on Flt3 expressing human peripheral blood monocyte is unclear. In the current study, we examined the role of FL on cell survival and growth of peripheral blood monocytes and function of monocyte‐derived DCs. FL promoted monocyte proliferation in a dose‐dependent manner and prevented spontaneous apoptosis. FL induced ERK phosphorylation and a specific ERK inhibitor completely abrogated FL‐mediated cellular growth, while p38 MAPK, JNK, and AKT were relatively unaffected. Addition of FL to GM‐CSF and IL‐4 during DCs generation from monocytes increased the yield of DCs through induction of cell proliferation. DCs generated in the presence of FL expressed more costimulatory molecules on their surfaces and stimulated allogeneic T cell proliferation in MLR to a higher magnitude. Furthermore, FL partially antagonized IL‐10‐mediated inhibition on DCs function. Further characterization of FL actions may provide new and important information for immunotherapeutic approaches utilizing DCs. J. Cell. Physiol. 230: 1740–1749, 2015. © 2014 Wiley Periodicals, Inc.